The Impact of The Translation Movement in Peaceful Coexistence Among Muslims and others in Iraq of Second Abbasin Age (218-334 AH / 833-945AD) - Dr-Nawras Ahmed Kadhem Al-Musawi; Sawsan Ahmed Najeeb (Genius Journals, 2022)
The first age (132-218 A.H/ 750-833 A.D) is considered one of the flourishing eras that developed the Arabian intellect, due to transferring of other different science from different languages to Arabic, because of the urgent need of Muslims to be open other developed nation's culture as a result to the concern of abbasin khalifa in translating many required fields in what they need to in politics and social affairs like medicine, astronomy, mathematics, and philosophy, it was not only encouraging from khalifas but by all community categories people in Baghdad, Basrah and Kufa and all parts of the Islamic empire that led to overwhelming the spirit of coexistence and forgiveness among Muslims and ahill aldimmah
Keywords: Ahill Aldimmah; Basrah and Kufa; community categories people